Shopping mall operation method and device using audition method - KIM, JONG HO (2023)
The present invention relates to a method and device for operating a shopping mall using an audition method which comprises: an audition board creating portion generating an audition board which provides a profile pixel board area composed of at least one pixel, wherein a profile pixel board is composed of a plurality of pixels in a service providing device; one providing portion providing points as a reward according to a payment amount when a user uploads a user's profile image and personal information to an audition board area and makes a payment at the same time; the other providing portion providing points as a reward when other users view and click the profile image of the user who participates in an audition; one display portion displaying the popularity of audition participants clicked by users in real time; the other display portion uploading products of users or product owners who participate in sponsorship back as profiles and displaying the profiles and the product; a purchase portion in which the products that participate in sponsorship can be linked to a shopping mall and purchased by viewing and clicking on the audition participant's profile image; and a means for connecting the user who participates in the audition and receives the most points and a certain number of click points given over a certain period of time to an actual offline audition. Accordingly, anyone can become a model and shop easily and with fun. 본 발명은 프로필 픽셀판이 서비스 제공 장치에서 복수의 픽셀로 구성되고, 적어도 하나 이상의 픽셀로 구성된 프로필 픽셀판 영역을 제공하는 오디션판을 생성하는 오디션판 생성부와, 상기 오디션판 영역에 대한 사용자의 프로필 이미지 및 개인정보를 업로드하며 동시에 결제를 하게되면 보상으로 결제 금액에 따른 리워드로 포인트가 제공되는 제공부와, 다른 유저들이 오디션에 참가한 사용자의 프로필 이미지를 보고 클릭하면 보상으로 포인트가 제공되는 제공부와, 유저들이 클릭한 오디션 참가자 사용자의 인기도가 실시간으로 표시되어 나타나는 표시부와, 후원하기로 참여하는 유저 또는 제품주들의 제품들이 프로필로 다시 업로드 되어 프로필과 제품이 표시되어 나타나는 표시부와, 오디션 참가자의 프로필 이미지를 보고 클릭하여 후원하기 참여한 제품들이 쇼핑몰로 연계되어 구매할 수 있는 구매부와, 오디션에 참가한 사용자가 일정 기간 주어진 클릭 점수로 가장 많은 점수 및 일정한 점수를 받은 오디션 참가 사용자가 실제 오프라인 오디션으로 연결되는 수단을 포함한 오디션 방식을 활용한 쇼핑몰 운영방법 및 장치